Recurrent and transformation of borderline to malignant phyllodes tumour with osteoid differentiation: a case report and literature review - Navin Raj Balachandran; Norlia Abdullah; Muhammad Ishamuddin Ismail; Yin Ping Wong; Mohd Imree Azmi (Frontiers in Oncology, 2024)
Phyllodes tumours or cystosarcoma phyllodes are fibroepithelial tumours of the breast and represent 1% of breast tumours. A 20-year-old nullipara presented with an enlarging left breast mass over 6 months. Although widely excised, it was reported to be a 12 × 10 × 5.5-cm borderline phyllodes tumour with involvement of the superior and inferior margins. Seven months later, she presented with a new ipsilateral breast lump measuring 8.5 × 7.5 × 4.6 cm. She underwent a left mastectomy, a three-rib resection with titanic rods for the thoracic cage reconstruction, and a latissimus dorsi flap wound closure. Histopathology revealed a high-grade malignant phyllodes tumour with features of osteoid differentiation with the nearest deep margin measuring 3 mm. She developed metastasis to the ipsilateral axillary lymph nodes and contralateral lung 2 months postoperatively. She was given palliative radiotherapy 60 Gy in 30 fractions to the left axilla. She developed sudden lower-limb weakness due to spinal metastases. The symptoms resolved with radiotherapy to the thoracic spine (T4–T8). As the lesion continued to grow rapidly from the anterior chest wall encircling towards the back, it was deemed unresectable. She was given palliative chemotherapy (doxorubicin six cycles, followed by ifosfamide one cycle) but had disease progression. She passed away 3 months later. The mainstay of treatment for phyllodes tumour is excision with a minimal margin of 1 cm. Although margins were involved after the first surgery, she was followed up as the pathology was a borderline phyllodes. When the lump recurred and had transformed, despite extensive surgery, it returned shortly and progressed. A borderline phyllodes should be excised to obtain a minimal margin of 1 cm, even if it means performing a mastectomy, to minimise recurrence. A recurrence may undergo malignant transformation which is largely chemotherapy and radiotherapy resistant. This will result in a poor outcome and decreased survival.